Effects of pharmacopuncture with metamizole on postoperative pain and analgesic requirements in dogs undergoing ovariohysterectomy - Ariga, Bruno K.; Kanashiro, Gláucia P.; Vieira, Gabriela B.M.; Peruchi, Luiza G.; Nicácio, Gabriel M.; Cassu, Renata N. [UNESP] (Elsevier, 2025)
Objective: To compare the postoperative analgesic efficacy of metamizole injected at acupuncture points with intramuscular injection in dogs undergoing elective ovariohysterectomy. Study design: Prospective, randomized, blinded, controlled clinical study. Animals: Thirty-six healthy pet dogs. Methods: The anesthetic protocol included meperidine and dexmedetomidine, propofol, and isoflurane. Immediately after anesthetic induction and orotracheal intubation, dogs were randomly assigned to be given 25 mg kg-1 of metamizole, injected bilaterally at the acupuncture points Stomach 36, Spleen 6, and Liver 3 (AP-G, n = 12), intramuscularly (IM-G, n =12), or no metamizole treatment (Control-G, n = 12). In the AP-G, metamizole was diluted in saline solution to a final volume of 1.2 mL, and 0.2 mL was injected at each acupuncture point. Intraoperatively, intravenous fentanyl was given to control cardiovascular responses to nociception. Pain was assessed preoperatively, 0.5, 1, 2, 4, 6, 8, and 12 hours after extubation, using the short form of the Glasgow Composite Pain Scale (CMPS-SF). Morphine was given as rescue analgesia. Data were analyzed using the Fisher's exact test, Kaplan Meier curve, Tukey test, Kruskal–Wallis test, and Friedman test (p < 0.05). Results: Morphine was required in 16.6% (2/12), 50% (6/12), and 75% (8/12) of the dogs in the AP-G, IM-G, and Control-G, respectively, with significant differences recorded between AP-G and Control-G (p = 0.036). Lower CMPS-SF scores were recorded in the AP-G compared with the IM-G and Control-G from 1 to 4 hours (p = 0.001–0.003). Conclusions and clinical relevance: Pharmacopuncture with metamizole provides similar levels of analgesia, as indicated by rescue analgesic requirement, as intramuscular metamizole in healthy dogs undergoing ovariohysterectomy. This technique may be considered as an adjunctive analgesic strategy for postoperative pain management.
Keywords: acupuncture; dipyrone; pain; pharmacopuncture